Causes of infant mortality in last 5 years (2007-2011) in Belgaum city, India - Yadav,Sanjay Kumar (2013)
ABSTRACT: Background and objectives: Despite massive efforts that, have been employed for maternal child health care, newborn care remains less likely address issue and this impacts negatively on MDG which pledges to reduce infant mortality by the year 2015. The present study was undertaken to assess the causes of the infant mortality. Materials and methods: The present retrospective study was conducted in five Urban Health Centres (UHCs) of the District Health Office, Belgaum City from March to December 2012. The causes of Infant death during 2007 to 2011 were retrieved from DHO covering five UHCs. To supplement the record based information, primary information regarding the causes of infant death was gathered by interviewing 20% of the mothers whose infants were died from two clusters namely, Azam Nagar cluster of Ashok Nagar UHC and Slum area of Rukmini Nagar UHC were conveniently selected. Results From 2007 to 2011, a total of 38,753 deliveries were conducted. Of them, 38462 were live births and 291 were still births. Total 339 infant death were recorded during this period. Overall IMR was calculated as 8.81/1000 live births for the given five years. During 2007-08 the IMR was 6.52 /1000 live births that increased to 9.31/1000 live births during 2008-09 and remained steady during 2009-10 (9.51/1000 live births) and 2010-11 (9.78/1000 live births) whereas, there was marginal reduction in IMR in the year 2011-12 (8.69 per 1000 live births). Conclusion: The leading cause of infant death was birth asphyxia (29.20%) followed by septicemia (18.29%), low birth weight (15.63%) and prematurity (11.21%). Findings from the verbal autopsy with mothers revealed similar trends in the causes of IMR. The most common cause of infant death was birth asphyxia (29.41%) followed by septicemia (17.65%), low birth weight (16.18%) and prematurity (11.76%). Key words: Birth asphyxia; Infant mortality; Verbal autopsy